2016
DOI: 10.3389/fnhum.2016.00266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hand-Omitted Tool Motion on mu Rhythm Suppression

Abstract: In the present study, we investigated the effect of the image of hands on mu rhythm suppression invoked by the observation of a series of tool-based actions in a goal-directed activity. The participants were 11 university students. As a source of visual stimuli to be used in the test, a video animation of the porcelain making process for museums was used. In order to elucidate the effect of hand imagery, the image of hands was omitted from the original (“hand image included”) version of the animation to prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Pfurtscheller et al indicated that mu suppression widely occurred on the somatic sensory cortex in the lower band, regardless of the type of movement, whereas in the upper band, the suppression occurred more limitedly, depending on the type of arm movement [14]. Furthermore, it has been reported that the mu wave upper band shows specific responses, correlated with object-oriented actions [15], social interactions [16], and actions with high target orientation using hands or tools [17].…”
Section: Introductionmentioning
confidence: 99%
“…Pfurtscheller et al indicated that mu suppression widely occurred on the somatic sensory cortex in the lower band, regardless of the type of movement, whereas in the upper band, the suppression occurred more limitedly, depending on the type of arm movement [14]. Furthermore, it has been reported that the mu wave upper band shows specific responses, correlated with object-oriented actions [15], social interactions [16], and actions with high target orientation using hands or tools [17].…”
Section: Introductionmentioning
confidence: 99%